An investigation into the syntactic and lexico-sematic features of indications and contra-indications in english and vietnamese medical package inserts - Lê, Nguyên Ngọc; Nguyễn Thị Quỳnh Hoa (ĐHĐN : ĐHĐN., 2015)
Based on the theories of syntactic and lexico-semantic features, this study makes an investigation into indications and contra-indications in English and Vietnamese medical package inserts. It is an attempt to discover some typical syntactic and lexico-semantic features and then find out the similarities and differences between them to suggest some implications for using medicine, teaching and learning the language skills in the medical field. In this study, in order to achieve the set goal, the author decides to use a combination of several research methods such as descriptive method, analytic method and comparative method. The data collected in this study, up to 250 samples in English and 250 samples in Vietnamese, were picked up both in printed medical package inserts manufactured in the USA, the UK and Vietnam, which have the average length ranging from 75 to 150 words. The charateristics of indications and contra-indications in terms of syntax and lexico-semantics presented in the study help to attract the readers’ attention to focused information, and also help the readers receive the indications and contra-indications as quickly as possible. It can also be seen that both languages used in indications and contra-indications use the strong impressions, emphasis to what they tend to focus on. Hopefully, the result of the study can be somewhat beneficial for the teaching and learning of English medical language. This study may also be helpful for the readers in comprehending the indications and contraindications in both English and Vietnamese medical package inserts.
Keywords: syntactic and lexico-sematic features of indications and contra-indications in english and vietnamese medical package inserts; syntactic -- lexico-sematic features